2017
DOI: 10.1213/xaa.0000000000000432
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of a Patient With an Intrathecal Drug Delivery Device Infusing Ziconotide

Abstract: Intrathecal ziconotide is used for the treatment of chronic pain and is delivered by an implanted drug delivery device. Anesthesiologists should be familiar with the perioperative management of the pump as well as the potential adverse events related to continued ziconotide infusion during general anesthesia. A case is presented demonstrating the perioperative management of an intrathecal drug delivery device infusing ziconotide in a patient presenting for radical cystectomy with pelvic lymphadenectomy and ile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although case reports and small case series can give valuable information and should therefore be published (recent examples are the papers by de la Calle Gil et al., ; Heifets et al., ; Horazeck et al., ; Lanzillo et al., ; Lux, ; Narain et al., ; Obafemi and Roth, ; Patel et al., ; Phan and Waldfogel, ; Pozzi et al., ; Russo et al., ; Staquet et al., ; Voirin et al., ), ‘real life’ data from larger cohorts such as the Registry of Intrathecal Ziconotide Management (PRIZM) (Deer et al., ) are more valuable. A recent interim analysis of the PRIZM study showed that, after 12 months of treatment, 34.8% of patients on ziconotide experienced ≥30% pain intensity reduction (Deer et al., ).…”
Section: Is Ziconotide Really That Effective In Clinical Practice?mentioning
confidence: 99%
“…Although case reports and small case series can give valuable information and should therefore be published (recent examples are the papers by de la Calle Gil et al., ; Heifets et al., ; Horazeck et al., ; Lanzillo et al., ; Lux, ; Narain et al., ; Obafemi and Roth, ; Patel et al., ; Phan and Waldfogel, ; Pozzi et al., ; Russo et al., ; Staquet et al., ; Voirin et al., ), ‘real life’ data from larger cohorts such as the Registry of Intrathecal Ziconotide Management (PRIZM) (Deer et al., ) are more valuable. A recent interim analysis of the PRIZM study showed that, after 12 months of treatment, 34.8% of patients on ziconotide experienced ≥30% pain intensity reduction (Deer et al., ).…”
Section: Is Ziconotide Really That Effective In Clinical Practice?mentioning
confidence: 99%